Intra-Tumoral Delivery of IL-27 Using Adeno-Associated Virus Stimulates Anti-tumor Immunity and Enhances the Efficacy of Immunotherapy - Hu, Aiyan; Ding, Miao; Zhu, Jianmin; Liu, Jin-Qing; Pan, Xueliang; Ghoshal, Kalpana; Bai, Xue-Feng (Frontiers in Cell and Developmental Biology, 2020)
IL-27 is an anti-inflammatory cytokine that has been shown to have potent anti-tumor activity. We recently reported that systemic delivery of IL-27 using recombinant adeno-associated virus (rAAV) induced depletion of Tregs and significantly enhanced the efficacy of cancer immunotherapy in a variety of mouse tumor models. A potential caveat of systemic delivery of IL-27 using rAAV is that there is no practical method to terminate IL-27 production when its biological activity is no longer needed. Therefore, in this work, we tested if directly injecting AAV-IL-27 into tumors could lead to similar anti-tumor effect yet avoiding uncontrolled IL-27 production. We found that high levels of IL-27 was produced in tumors and released to peripheral blood after AAV-IL-27 intra-tumoral injection. AAV-IL-27 local therapy showed potent anti-tumor activity in mice bearing plasmacytoma J558 tumors and modest anti-tumor activity in mice bearing B16.F10 tumors. Intra-tumoral injection of AAV-IL-27 induced infiltration of immune effectors including CD8+ T cells and NK cells into tumors, caused systemic reduction of Tregs and stimulated protective immunity. Mechanistically, we found that IL-27 induced T cell expression of CXCR3 in an IL-27R-dependent manner. Additionally, we found that AAV-IL-27 local therapy had significant synergy with anti-PD-1 or T cell adoptive transfer therapy. Importantly, in mice whose tumors were completely rejected, IL-27 serum levels were significantly reduced or diminished. Thus, intra-tumoral injection of AAV-IL-27 is a feasible approach that can be used alone and in combination with anti-PD-1 antibody or T cell adoptive transfer for the treatment of cancer.